Parameter Tuning Of An Active Force Control For Cmg-Based Controlled Small Satellite - Linghan, Samanaseh (Universiti Sains Malaysia, 2019)
A control moment gyroscope (CMG) system is the most appropriate actuator to be actualized in attitude determination and control system (ADCS) of small satellite. These actuators can provide unique torque, angular momentum and slew rate capabilities to small satellites without any increase in power, mass or volume. This will help small satellites become more agile. A four single gimbal control moment gyroscope (4-SGCMG) is actualize by owing to its efficiency and plays a significant role in attitude control of agile small satellite. However, the efficiency of the CMG system is limited to in executing rapid attitude maneuver and high precision pointing due to external disturbance torques from space environment and internal disturbance of actuator. Hence, an Active Force Control (AFC) technique is enforced and integrated with proportional-derivative (PD) controller to enhance ADCS by rejecting the disturbance torques robustly. In this research, tuning the mass parameter of the dynamic system and the AFC gain, the robustness of AFC technique is triggered. So that, the PD-AFC attitude control scheme able to command the CMG system to give suitable control torque to fulfill the satellite mission. The singularity robust (SR) steering law is integrated with CMG system in order to neglect the singularity state of CMG system by setting the initial gimbal angle, that allowing space missions to be successfully executed. All mathematical models were made amenable for numerical simulations in Matlab®/Simulink® in order to study the effect of AFC parameters tuning on the attitude control performance of the satellite by considering the presence of external disturbance torques.